2009
DOI: 10.1287/mnsc.1090.1044
|View full text |Cite
|
Sign up to set email alerts
|

Poker Player Behavior After Big Wins and Big Losses

Abstract: We find that experienced poker players typically change their style of play after winning or losing a big pot-most notably, playing less cautiously after a big loss, evidently hoping for lucky cards that will erase their loss. This finding is consistent with Kahneman and Tversky's break-even hypothesis and suggests that when investors incur a large loss, it might be time to take a vacation or be monitored closely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 33 publications
3
43
1
2
Order By: Relevance
“…Overall, the results of these studies do not support earlier findings that Internet gambling is more addictive than land-based gambling [15,16,17,18,19,20,21,22,23,24,25,26]. Meanwhile, a growing body of research has focused on analyzing data sets of gambling accounts provided by various gambling operators [12,13,27,28]. …”
Section: Introductioncontrasting
confidence: 65%
“…Overall, the results of these studies do not support earlier findings that Internet gambling is more addictive than land-based gambling [15,16,17,18,19,20,21,22,23,24,25,26]. Meanwhile, a growing body of research has focused on analyzing data sets of gambling accounts provided by various gambling operators [12,13,27,28]. …”
Section: Introductioncontrasting
confidence: 65%
“…In an interesting study by Smith, Levere, and Kurtzman (2009), poker players were found to change their strategy after significant wins or losses. Big losses were followed by playing less cautiously, with players tending to be more aggressive compared to their behaviour after big wins.…”
Section: Introductionmentioning
confidence: 99%
“…By electronically tracking and recording gambling behaviour, researchers non-intrusively obtain data from large gambling populations. Several gambling studies have now utilized account-based player gambling data (Leino et al, 2014;Ma, Kim, & Kim, 2014;Narayanan & Manchanda, 2012;Smith, Levere, & Kurtzman, 2009). Through the use of account-based gambling data, it has been found that gambling behaviour is associated with structural game characteristics (Leino et al, 2014), immediate and long-term gains and losses (Ma et al, 2014;Narayanan & Manchanda, 2012), subsequent gambling style after big wins and losses (Smith et al, 2009) and the decision to close a gambling account due to gambling-related problems (Xuan & Shaffer, 2009).…”
Section: Introductionmentioning
confidence: 99%